How should reflection be supported in higher education? — A meta-analysis of reflection interventions. Issue 1 (2nd January 2022) - Guo, Lin
ABSTRACT: The present study adopted a meta-analytic approach to evaluate reflective interventions that were conducted with the intention to promote learning outcomes in higher education, using controlled experimental designs. A systematic search of the extant literature yielded 23 articles, comprising 23 effect sizes and a total of 2010 participants. Under a random-effects model, the results showed that reflective interventions had a positive and significant medium-sized effect ( g = 0.56, SE  = 0.06) on learning outcomes. The moderator analyses revealed that the effect varied as a function of intervention duration, peer interaction and reflective activities. These findings underscore the importance of fostering reflective thinking and refining design principles for reflective scaffolding.